Evaluation of micronized progesterone influence on breast density - Sobczuk, Anna; Stefańczyk, Ludomir; Pertyński, Tomasz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
Increased breast density in some women makes the evaluation of mammography results more difficult and that is why this becomes an important clinical problem. The aim of our study was to evaluate the influence of micronized progesterone, used as a substitution treatment in the second phase of the cycle in pre- and perimenopausal women, on breast density measured during mammography. The second phase substitution therapy was administered in 26 women included into the study. Micronized progesterone was applied 3 times a day at a dose of 50 mg between the 16th and the 25th day of a cycle for 6 months. When comparing breast density after 6 months of progesterone treatment with values before the therapy we noted a 19.2% decrease in breast density in the study group.